Impact Multicultural Education: Case study in Social Studies Learning - Miftakhul, Amin; Harmanto, Harmanto; Sunarto, Sunarto (International Journal for Educational and Vocational Studies, 2020)
This study intends to describe the impact of multicultural education in Social Studies Learning of junior high school. This type of research is qualitative with the method descriptive. The subject of this research is the component (Teacher and students) Middle-School 6 Sidoarjo. Based on the results of data analysis and discussion shows that Multicultural education in practice for social studies education learning in the classroom runs smoothly and students can be carefully conditioned to have an effect and have an impact, among others: Be tolerant in accepting all differences, because the difference is God's grace, does not discriminate (discriminate) friends who different beliefs, do not force others in terms of beliefs (religion), give freedom to others to choose beliefs (religion), do not interfere with other people with different beliefs when they worship, keep on interacting and behaving well with people who have different beliefs in worldly matters, respect others who are worshiping, do not hate and hurt the feelings of someone who has different beliefs or opinions from us. It is hoped that these forms of tolerance will bring positive energy which will not trigger disputes or quarrels between students.